Induction of Humoral Immunity Through the Enhancement of IgM Production in Murine Splenic Cells by Ethanolic Extract of Seed of Piper nigrum L. (Journal of Scientific Research, 2012)
The immunostimulating activity of 70% ethanololic extract of P. nigrum L. was investigated by measuring the production of immunoglobulin M (IgM) and the proliferation of murine splenic cells in vitro. The production of IgM in cultured supernatants was determined by an enzyme-linked immunosorbent assay (ELISA) and proliferation of cells was measured by 3-(4,5-dimethylthiazol-2-y)-2,5-diphenylterazolium bromide (MTT) assay. The extract at the doses of 0.01 and 0.1 mg/ml significantly augmented the production of polyclonal IgM production (0.3206 and 0.5014 µg/ml, respectively) compared to control (0.1465 µg/ml). No dose of the extract could remarkably increase the proliferation of splenocytes. Thus, the present study clearly demonstrates the immunostimulating activity of ethanololic extract of Piper nigrum; exhibited mainly by the differentiation of B cells to plasma cells rather than proliferation of splenocytes.© 2012 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved.doi: http://dx.doi.org/10.3329/jsr.v4i3.10485 J. Sci. Res. 4 (3), 751-756 (2012)